2015
DOI: 10.1093/hmg/ddv368
|View full text |Cite
|
Sign up to set email alerts
|

Two novel COLVI long chains in zebrafish that are essential for muscle development

Abstract: Collagen VI (COLVI), a protein ubiquitously expressed in connective tissues, is crucial for structural integrity, cellular adhesion, migration and survival. Six different genes are recognized in mammalians, encoding six COLVI-chains that assemble as two 'short' (α1, α2) and one 'long' chain (theoretically any one of α3-6). In humans, defects in the most widely expressed heterotrimer (α123), due to mutations in the COL6A1-3 genes, cause a heterogeneous group of neuromuscular disorders, collectively termed COLVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 69 publications
4
11
0
Order By: Relevance
“…They demonstrated that the morphants had axonal outgrowth deficits without a primary muscular involvement ( Zech et al, 2015 ). Similar findings concerning altered axonal growth were demonstrated in col6a2 and in col6a4 zebrafish morphants, which also displayed motor activity abnormalities and muscle defects ( Ramanoudjame et al, 2015 ). The various findings collected from the animal models described above emphasize the importance of in vivo studies for unraveling the novel roles of ColVI in specific tissues, such as the nervous system, and for revealing unexpected phenotypical outcomes of targeted mutations.…”
Section: Introductionsupporting
confidence: 73%
“…They demonstrated that the morphants had axonal outgrowth deficits without a primary muscular involvement ( Zech et al, 2015 ). Similar findings concerning altered axonal growth were demonstrated in col6a2 and in col6a4 zebrafish morphants, which also displayed motor activity abnormalities and muscle defects ( Ramanoudjame et al, 2015 ). The various findings collected from the animal models described above emphasize the importance of in vivo studies for unraveling the novel roles of ColVI in specific tissues, such as the nervous system, and for revealing unexpected phenotypical outcomes of targeted mutations.…”
Section: Introductionsupporting
confidence: 73%
“…In another study, depletion of collagen VI ( COLVI ), a protein crucial for structural integrity, cellular adhesion, migration and survival, resulted in reduced lipidation of Lc3 and reduced expression of Beclin1, suggesting an overall inhibition of autophagy in these morphants, ultimately leading to muscle dysfunction [ 74 ]. The role of autophagy in survival of hematopoietic cells was observed in a disrupted ribosome biogenesis model of zebrafish where rps19 was ablated using translation morpholino [ 75 , 76 ].…”
Section: Genome Editing Techniquesmentioning
confidence: 99%
“…Although similar reduction in Beclin1 protein levels has been reported in muscle biopsies from patients, analysis of the autophagic flux in human muscle cells would provide a better insight into the pathogenic role of autophagy. Interestingly, autophagy induction also seems to be impaired in COLVI-deficient zebrafish, but was not related to abnormal Akt activation [ 158 ].…”
Section: Neuromuscular Disorders Related To Abnormal Autophagy Inductmentioning
confidence: 99%